VOCATIONAL SCHOOL-INDUSTRY PARTNERSHIP IN IMPROVING GRADUATE COMPETENCY - AR, Murniati; Usman, Nasir; Azizah, Azizah (Jurnal Ilmiah Peuradeun, 2016)
A wide variety of educational reform on vocational education in accordance with the policy of link and match requires the schools to do the partnership to encourage the improvement of graduate competency and the demands of the relevance of education to the job needs. The purpose of this research is to illustrate and analyze the partnership strategy of vocational schools with the business world in its efforts to improve the graduate competency. This research has been held at SMK 3 Banda Aceh using qualitative descriptive approach. The instrument in this research is a researcher itself. This is because in qualitative approach, the researchers are essential instruments. As key instruments, researchers have to create their own set of the guidelines, observation, interview and documentary of appraisal guidelines that is used as a general guide in the process of recording. The results of the study show that the strategies adopted by SMK in forge cooperation with the world of business and industry are through the establishment of the cooperation program, working mechanism and analysis of factors that affect the holding of cooperation between the two parties.